Vacuolar/lysosomal proteolysis: proteases, substrates, mechanisms - Knop, Michael; Rupp, Steffen; Wolf, Dieter H. (Current opinion in cell biology, 2004)
Proteolysis is an essential post-transcriptional process. The lysosome/vacuole is the central organelle for non-specific proteolysis in eukaryotes. Most proteases that work in the lysosome enter it via the secretory pathway. The bulk of proteins to be degraded enter this proteolytic compartment via endocytosis and autophagocytosis. Our understanding of the mechanisms involved in these processes has increased considerably, and the information obtained in these studies has enabled new, specific proteolytic pathways to be investigated in other cellular compartments, particularly in the cytoplasm.